PENGARUH RUANG, WADAH DAN PERIODE SIMPAN TERHADAP PERKECAMBAHAN BENIH KESAMBI ( Schleichera oleosa Merr.) - Eliya Suita; Endang Ismiati (Jurnal Pemuliaan Tanaman Hutan, 2011)
Tree seed  for planting program are not always available in sufficient quantity in right time. Seed storage efforts at the optimum conditions for plant propagation material are needed to meet those needs. Referring to the theory, this experiment was carried out to investigate the appropriate room of starage, container of storage, and periods of storage to maintain the germination of kesambi seeds. Experimental design used was split plot design with three factors such as room of storage (ambient room, temperature 27-30 0C and relative humidity 60-70%, air conditioned room, temperature 18-20 OC). Container of storage (plastic bag andblacu bag)and periods of storage (1 month , 3 months, and 5 months) . Every unit of treatment contain 25 seed and replication 4 times. The results of this research indicated that the viability of the kesambi seed can be maintained for 3  month using blacu bag as sinby an average g blacu bag as container with    the germanition percentage and  speed of ngeminiton by an average of (75% and 4.14% and 4.14 KN /etmal ) and the moisture content 7.79%